The Effectiveness of the Different Patterns of the Digital Story in the Development Linguistic Intelligence Skills and Mindfulness Among Jordanian Primary Students During the Corona Pandemic - Aldalalah, Osamah Mohammad Ameen (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The purpose of this study was to investigate effectiveness of the different pattern of the digital story in the development linguistic intelligence skills and Mindfulness in Jordanian primary students during the Corona pandemic. Quasi experimental factorial design was adopted in this research. The researcher designed two patterns of the digital story in the Arabic language course. The study sample consisted of 43 students and were randomly (simple random sample) selected. The study sample was divided into two groups. The first group consisted of 23 students who studied through a written digital story, as for the second group, it consisted of 20 students who studied through the digital audiovisual story. The dependent variables were the linguistic intelligence skills and Mindfulness. The researcher used two scales. The first is to measure linguistic intelligence skills, and the second is to measure mindfulness. Data were collected and appropriate statistical analysis performed. ANCOVA was used to determine the significant differences among the two groups. Analyses of covariance (ANCOVA) were performed to examine the main effects of the independent variables on the dependent variables. The findings of this study showed that students using the digital audiovisual story mode performed significantly better than those students using the written digital story in the linguistic intelligence skills, and mindfulness.